Islamic Course Program (Program Pendamping Keagamaan) in the Integration-Interconnection of Science and Religion in Faculty of Science and Technology UIN Sunan Kalijaga Yogyakarta - Laras Mawarti (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2017)
The change of the Institute to University proclaimed a new paradigm in viewing and conducting studies on the religious sciences and general sciences, namely the integration-interconnection paradigm. The scientific paradigm of integration-interconnection is expected to be the answer or response to the dichotomy of general education and religious education in Islamic civilization. Data on the role of PPK in the Integration-Interconnection science and religion in faculty of Science and Technology are obtained through questionnaires. Islamic Course Program (PPK) UIN Sunan Kalijga is an effort to realize the integration-interconnections between science and religion. This program can also disregard religious radicalism among Science and Technology students. The benefits of PPK include the increasing of students religious knowledge: strengthen the aqidah, good morality and worship. PPK enhances students' ability to read the Qur'an, memorize the Qur'an and understand the Qur'an. So science students have a balance between science and religion.